REPRESENTASI PARIWISATA BERKELANJUTAN DALAM NOVEL AKAR KARYA DEE LESTARI: KAJIAN SASTRA PARIWISATA - Ummu Kalsum R; Andi Karman; Aslan Abidin (STKIP Subang, 2026)
This study aims to analyze the representation of sustainable tourism elements in Dee Lestari's novel Akar using the Literary Tourism theory proposed by Prof. I Nyoman Darma Putra. This theoretical approach is used to examine the dialectical relationship between literary texts and destination image-building as well as tourism practices. The research method employed is descriptive qualitative with hermeneutic analysis techniques, focusing on the exploration of textual meaning, context, and potential extrinsic impacts. The results show that the novel Akar carefully represents two main destinations Java (Indonesia) and Brazil through the construction of lyrical natural imagery, profound ecological wisdom, and implicit criticism of environmental exploitation. This representation not only builds a strong destination image with an eco-spiritualism nuance but also has great potential to trigger sustainable literary tourism. However, the analysis also reveals a romanticization and commodification of local wisdom that needs to be read critically. These findings reinforce Darma Putra's thesis that contemporary literature functions as an effective soft power medium in promoting conservation values and shaping responsible tourist perceptions.